Prediction by Young Autistic Children from Visual and Spoken Input. - Mathée-Scott, Janine; Prescott, Kathryn E.; Pomper, Ron; Saffran, Jenny; Weismer, Susan Ellis (Journal of Autism & Developmental Disorders, 2026)
Recent theoretical accounts suggest that differences in the processing of probabilistic events underlie the core and associated traits of autism spectrum disorder (ASD). These theories hypothesize that autistic individuals are differentially impacted by disruptions in probabilistic input relative to neurotypical peers. According to this view, autistic individuals assign disproportionate weight to prediction errors such that novel input is overweighted relative to the aggregation of prior input; this is referred to as 'hyperplasticity' of learning. Prediction among autistic individuals has primarily been examined in nonverbal, visual contexts with older children and adults. The present study examined 32 autistic and 32 cognitively-matched neurotypical (NT) children's ability to generate predictions and adjust to changes in predictive relationships in auditory stimuli using two eye gaze tasks. In both studies, children were trained and tested on an auditory-visual cue which predicted the location of a reward stimulus. In Experiment 1 the cue was non-linguistic (instrumental sound) whereas in Experiment 2 the cue was linguistically-relevant (speaker gender). In both experiments, the cue-reward contingency was switched after the first block of trials, and predictive behavior was evaluated across a second block of trials. Analyses of children's looking behavior revealed similar performance in both groups on the non-linguistic task (Exp. 1). In the linguistically-relevant task (Exp. 2), predictive looking was less disrupted by the contingency switch for autistic children than NT children. Results suggest that autistic children may demonstrate hyperplastic learning in linguistically-relevant contexts, relative to NT peers.